Share repurchases as a form of payout for shareholders - Mieczysław Kowerski (e-Finanse: Financial Internet Quarterly, 2011)
Share repurchase happens when a company repurchases its own shares for any purpose determined by the general meeting of shareholders, including their further sale. Share repurchase is like dividend payout a form of transferring profit to shareholders. However, contrary to dividends, it is quite a new legal institution, which gained importance in developed capital markets as late as in the last twenty years of the 20th century. This article presents the development of the institution of share repurchasing and changing relations between purchasing shares and paying out dividends in developed capital markets. It also presents the legal situation concerning share repurchase in Poland, pointing out that only the regulations introduced in 2008 adjusted Polish legal solutions to those valid in developed capital markets.
Keywords: G35; G15; 330; payout policy; share repurchase; dividend